Screening of a genome‐reduced Corynebacterium glutamicum strain library for improved heterologous cutinase secretion. Issue 6 (6th September 2020) - Hemmerich, Johannes; Labib, Mohamed; Steffens, Carmen; Reich, Sebastian J.; Weiske, Marc; Baumgart, Meike; Rückert, Christian; Ruwe, Matthias; Siebert, Daniel; Wendisch, Volker F.; Kalinowski, Jörn; Wiechert, Wolfgang; et al.
Summary: The construction of microbial platform organisms by means of genome reduction is an ongoing topic in biotechnology. In this study, we investigated whether the deletion of single or multiple gene clusters has a positive effect on the secretion of cutinase from Fusarium solani pisi in the industrial workhorse Corynebacterium glutamicum . A total of 22 genome‐reduced strain variants were compared applying two Sec signal peptides from Bacillus subtilis . High‐throughput phenotyping using robotics‐integrated microbioreactor technology with automated harvesting revealed distinct cutinase secretion performance for a specific combination of signal peptide and genomic deletions. The biomass‐specific cutinase yield for strain GRS41_51_NprE was increased by ~ 200%, although the growth rate was reduced by ~ 60%. Importantly, the causative deletions of genomic clusters cg2801‐cg2828 and rrnC ‐cg3298 could not have been inferred a priori . Strikingly, bioreactor fed‐batch cultivations at controlled growth rates resulted in a complete reversal of the screening results, with the cutinase yield for strain GRS41_51_NprE dropping by ~ 25% compared to the reference strain. Thus, the choice of bioprocess conditions may turn a 'high‐performance' strain from batch screening into a 'low‐performance' strain in fed‐batch cultivation. In conclusion, future studies are needed in order to understand metabolic adaptations of C. glutamicum to both genomic deletions and different bioprocess conditions. Abstract : The construction of microbial platform organisms by means of genome reduction is an ongoing topic in biotechnology. In this study, we investigated whether the deletion of single or multiple gene clusters has a positive effect on the secretion of cutinase from Fusarium solani pisi in the industrial workhorse Corynebacterium glutamicum . A total of 22 genome‐reduced strain variants were compared applying two Sec signal peptides from Bacillus subtilis . High‐throughput phenotyping using robotics‐integrated microbioreactor technology with automated harvesting revealed distinct cutinase secretion performance for a specific combination of signal peptide and genomic deletions. Strikingly, bioreactor fed‐batch cultivations at controlled growth rates resulted in a complete reversal of the batch screening results, with the cutinase yield for strain GRS41_51_NprE dropping by ~ 25% compared to the reference strain. Thus, the choice of bioprocess conditions may turn a "high‐performance" strain from batch screening into a "low‐performance" strain in fed‐batch cultivation.